Psychiatric Morbidity among Primary Caregivers of Children with Neurodevelopmental Disorders at a Teaching Hospital in Kenya - Louise Namusonge Lusimbo; Daniel Kinyanjui; Irene J. Chesire (Pan-African Journal of Health and Environmental Science)
Background: Psychiatric morbidities are often underdiagnosed among the primary caregivers of children with neurodevelopmental disorders who attend child clinics; however, they are frequent and are associated with adverse outcomes. An integrated management program, which is an evidence-based approach to psychiatric morbidity management, remains an exception in most hospital settings. This study investigated the prevalence of psychiatric morbidity and its associated factors among primary caregivers of children with neurodevelopmental disorders.